Changes of Intracellular Porphyrin, Reactive Oxygen Species, and Fatty Acids Profiles During Inactivation of Methicillin-Resistant Staphylococcus aureus by Antimicrobial Blue Light - Wu, Jiaxin; Chu, Zhaojuan; Ruan, Zheng; Wang, Xiaoyuan; Dai, Tianhong; Hu, Xiaoqing (Frontiers in Physiology, 2018)
Antimicrobial blue light (aBL) has attracted increasing interest for its antimicrobial properties. However, the underlying bactericidal mechanism has not yet been verified. One hypothesis is that aBL causes the excitation of intracellular chromophores; leading to the generation of reactive oxygen species (ROS) and the resultant oxidization of various biomolecules. Thus, monitoring the levels of redox-sensitive intracellular biomolecules such as coproporphyrins, as well as singlet oxygen and various ROS may help to uncover the physiological changes induced by aBL and aid in establishing the underlying mechanism of action. Furthermore, the identification of novel targets of ROS, such as fatty acids, is of potential significance from a therapeutic perspective. In this study, we sought to investigate the molecular impact of aBL treatment on methicillin-resistant Staphylococcus aureus (MRSA). The results showed that aBL (5–80 J/cm2) exhibited a bactericidal effect on MRSA, and almost no bacteria survived when 80 J/cm2 had been delivered. Further studies revealed that the concentrations of certain intracellular molecules varied in response to aBL irradiation. Coproporphyrin levels were found to decrease gradually, while ROS levels increased rapidly. Moreover, imaging revealed the emergence and increase of singlet oxygen molecules. Concomitantly, the lipid peroxidation product malondialdehyde (MDA) increased in abundance and intracellular K+ leakage was observed, indicating permeability of the cell membrane. Atomic force microscopy showed that the cell surface exhibited a coarse appearance. Finally, fatty acid profiles at different illumination levels were monitored by GC-MS. The relative amounts of three unsaturated fatty acids (C16:1, C20:1, and C20:4) were decreased in response to aBL irradiation, which likely played a key role in the aforementioned membrane injuries. Collectively, these data suggest that the cell membrane is a major target of ROS during aBL irradiation, causing alterations to membrane lipid profiles, and in particular to the unsaturated fatty acid component.